Challenges and Opportunities of the Modern Risk Society: Socio-Cultural, Economic and Legal Aspects 2021
DOI: 10.46489/caotm-21042612
|View full text |Cite
|
Sign up to set email alerts
|

Legal Problems of International Settlement of Investment Disputes as a Factor of Financial Ensuring Business Safety

Abstract: International investment disputes between states arise in connection with different interpretation and application of the provisions of international investment treaties and agreements. As the matter of fact, such disputes also appear from violations of the provisions of international investment agreements that may prejudice the rights of foreign private investors. Since a dispute arises from a violation of investor rights, most modern investment treaties provide for the right of investors to submit a dispute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The issue of payment of compensation in the event of nationalisation or other seizure of foreign property in a compulsory aspect is only one of the possible grounds for the emergence of an investment conflict. For example, such cases may include early termination of the concession plan agreement or modification of its terms, unjustified refusal to register an enterprise with foreign investments, or refusal to move profits abroad (Bryhinets & Kovalova, 2021). The Washington Convention (1965) provides that arbitration between an investor and the state can be applied in the event of a violation by the state of the investor's rights arising from an investment treaty or international law.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of payment of compensation in the event of nationalisation or other seizure of foreign property in a compulsory aspect is only one of the possible grounds for the emergence of an investment conflict. For example, such cases may include early termination of the concession plan agreement or modification of its terms, unjustified refusal to register an enterprise with foreign investments, or refusal to move profits abroad (Bryhinets & Kovalova, 2021). The Washington Convention (1965) provides that arbitration between an investor and the state can be applied in the event of a violation by the state of the investor's rights arising from an investment treaty or international law.…”
Section: Methodsmentioning
confidence: 99%
“…An analysis by the Seoul Convention (1985) confirms that it has created a single mechanism for protecting foreign investment, which is based on special regulatory principles. The main part of investment disputes considered by ICSID is disputes related to concession agreements and the immutability of their terms; therefore, it can be concluded that there is a wide range of grounds for investment disputes (Bryhinets & Kovalova, 2021). Each of the international bodies for resolving such disputes has its own advantages and disadvantages.…”
Section: Methodsmentioning
confidence: 99%